Text Based Approach For Similar Traffic Incident Detection from Twitter - ermawati, Myrna; Buliali, Joko Lianto (Lontar Komputer : Jurnal Ilmiah Teknologi Informasi; Vol. 9, No. 2 August 2018, 2018)
Microblog has been used as an information source to detect real-world event. Several related studies retrieved road traffic event based on textual content. Not only detect traffic incident, we found that it is necessary to recognize statuses with similar traffic incident content. Better representation of traffic information will help the handling of traffic incident by related parties. This study proposes text-based approach for identification of similar traffic incident from twitter posts. The proposed approach performs traffic incident information extraction and calculates information’s weight based on textual similarity upon traffic incident information gained. We evaluate the proposed method by using a traffic incident information retrieval system. We used Indonesian language corpus contains traffic incident tweets data. Best average f-measure 70% was achieved by retrieval system that tested using Jaccard coefficient. Therefore text matching such as Jaccard coefficient is more suitable to be implemented in very short text document such as extracted tweet document. The experiment result gives the conclusion that the proposed approach can be implemented for identification of similar traffic incident information from Twitter.